LoRa-Based Ground Sensor Terminal for L-Band Satellite IoT Applications - Mohd Farid Omar,; Zafirah Faiza,; Ali, Fatimah Zaharah; Mardeni Roslee,; Muhammad Syazwan Johari,; Mohamad Huzaimy Jusoh, (International Journal of Integrated Engineering, 2024)
This paper discusses the need for Internet of Things (IoT) solutions in remote places and the development of a LoRa-based Ground Sensor Terminal (GST) for L-Band Satellite IoT Applications. With a transmission range of 450 m, LoRa technology hinders connectivity in remote areas. GST adaptive frequency band designs are few. This project aims to modularly integrate numerous satellite modems into the GST and evaluate LoRa's maximum distance coverage. This research proposes an innovative and flexible ground sensor terminal design and evaluates LoRa performance in indoor, outdoor, and maximum range scenarios, including near-real-time satellite transmission results. This study shows that LoRa antennas can be upgraded to 5 dbi to improve connectivity and IoT applications in remote places. This investigation addresses the need for remote IoT solutions and advances in IoT technology.